Analisis Efisiensi Waktu Dan Biaya Pada Pelaksanaan Proyek Konstruksi Dengan Penambahan Jam Kerja Dan Penambahan Tenaga Kerja Menggunakan Metode Time Cost Trade Off - Mochdara K, Irfan; Adjam, Idhar; Altarans, Indra; Muhammad, Amiruddin Hi. (Jurnal Ilmiah Wahana Pendidikan, 2025)
The results of time and cost optimization in this studyusing the alternative of adding working hours resulted in a total completion time of 182days, which is 14 (7.14%) days faster than the normal time of 196 days, with a total project cost ofRp. 1,767,600,000.00, resulting in a cost efficiency of Rp. 232,559,067.27(12.62%). Meanwhile, using the alternative of adding manpower resulted in a totalcompletion time of 179 days, which is 17 (8.67%) days faster than the normal time witha total project cost of IDR 1,767,600,000.00, achieving a cost efficiency ofRp.7,870,582.09 (0.44%). Therefore, time and cost efficiency with the addition ofworking hours is more economical. The implications of this research provide recommendations for project managersin making decisions to accelerate work so that it is efficient in terms of time and cost.